A Zirconium Indazole Carboxylate Coordination Polymer as an Efficient Catalyst for Dehydrogenation‐Cyclization and Oxidative Coupling Reactions. Issue 1 (9th January 2020) - Sang, Xinxin; Hu, Xinyu; Tao, Rong; Zhang, Yilin; Zhu, Haiyan; Wang, Dawei
Abstract: Rational ligand design is crucial for achieving widespread applications of coordination polymers. The preparation, structural characterisation, and catalytic applications of zirconium (IV) coordination polymer (Zr‐IDA), which was derived from 1‐(carboxymethyl)‐1H‐indazole‐5‐carboxylic acid are reported. The Zr‐IDA catalyst contains porous and highly crystalline particles with a quasi‐spherical morphology around 100 nm in size, and Zr was coordinated with both O and N as shown by FT‐IR and XPS measurements. Importantly, the Zr‐IDA catalyst shows great activity, selectivity and stability in the oxidative coupling of benzyl cyanides with tert ‐butyl hydroperoxide to afford tert ‐butyl peresters, and the dehydrogenation cyclization of o ‐phenylenediamines with aromatic alcohols to afford 1, 2‐disubstituted benzimidazole derivatives. Mechanistic investigations were carried out to study these reactions and the developed catalytic system in more detail. Abstract : Take your time to design : Rational ligand design is crucial for achieving widespread applications of coordination polymers. The preparation, structural characterisation, and catalytic applications of zirconium (IV) coordination polymer (Zr‐IDA), which was derived from 1‐(carboxymethyl)‐1H‐indazole‐5‐carboxylic acid are reported. The Zr‐IDA catalyst contains porous and highly crystalline particles with a quasi‐spherical morphology around 100 nm in size. The Zr‐IDA catalyst shows great activity, selectivity and stability in the oxidative coupling and the dehydrogenation cyclization.